Tritium Mobility in the Environment Using Deuterium as an Analogue - DeHay-Turner, Brett (Université d'Ottawa / University of Ottawa, 2016)
Tritium is a radioisotope of hydrogen and a component of emissions from the nuclear industry. It is also a radioisotope of concern for human and environmental health. The near future could see an increase in tritium production as experimental fusion reactors initiate first plasma. The greatest risk pathway is human ingestion of edible plants grown near sites of tritium emissions as they can acquire high levels of organically bound tritium (OBT). Recent studies at a tritium Beta-light facility in Pembroke, Ontario, Canada characterized by tritiated hydrogen gas (HT) emissions have identified high OBT:HTO ratios that are not consistent with current tritium transfer models. This suggests that there is an unidentified physical, chemical, or biological mechanism generating OBT in plant tissue. Laboratory experiments have been undertaken using deuterium gas (D2) as an analogue for atmospheric HT in controlled plant exposure experiments, and compared the observations with short-term exposures at the SRBT facility. While the deuterium results did not uncover a hidden pathway or enrichment mechanism, the SRBT exposures showed elevated tissue free water tritium (TFWT) in stems and leaves in the presence of atmospheric HT, and lacking HTO in both soils and surrounding air. This study proposes that hydrogenase activity in microbial communities hosted within the laminar boundary layer on the leaf surface, are responsible for HT oxidation to HTO that contributes directly to leaf waters used in photosynthesis.
Keywords: tritium; organically bound tritium; obt; deuterium; tritiated water; hto; tritiated hydrogen gas; ht